Natural history collecting. - Harris, Reg.; Thornley, Peter (New York, Grosset & Dunlap, 1972)
This survey of natural history includes techniques for collecting plant, animal, and geological specimens.
Includes bibliographical references.
Keywords: Biological specimens -- Collection and preservation; Geological specimens -- Collection and preservation; Natural history